2006
DOI: 10.1016/j.cell.2006.05.042
|View full text |Cite
|
Sign up to set email alerts
|

FOXP3 Controls Regulatory T Cell Function through Cooperation with NFAT

Abstract: Antigen stimulation of immune cells activates the transcription factor NFAT, a key regulator of T cell activation and anergy. NFAT forms cooperative complexes with the AP-1 family of transcription factors and regulates T cell activation-associated genes. Here we show that regulatory T cell (Treg) function is mediated by an analogous cooperative complex of NFAT with the forkhead transcription factor FOXP3, a lineage specification factor for Tregs. The crystal structure of an NFAT:FOXP2:DNA complex reveals an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

52
1,030
8
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,037 publications
(1,110 citation statements)
references
References 51 publications
52
1,030
8
8
Order By: Relevance
“…Mechanistically, the requirement for high and stable Foxp3 levels for conversion of CD4 + CD25 -cells into Treg is consistent with the recent demonstration that Foxp3 controls the Treg function by forming a DNA-binding complex with NFAT, which in turn results in repression of the NFAT:AP-1-dependent transcription of several activation-associated genes [22]. Thus, in Foxp3-transduced CD4 + CD25 -cells, competition between the retrovirally introduced Foxp3 and naturally expressed AP-1 for NFAT binding could be an important event for lineage determination.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Mechanistically, the requirement for high and stable Foxp3 levels for conversion of CD4 + CD25 -cells into Treg is consistent with the recent demonstration that Foxp3 controls the Treg function by forming a DNA-binding complex with NFAT, which in turn results in repression of the NFAT:AP-1-dependent transcription of several activation-associated genes [22]. Thus, in Foxp3-transduced CD4 + CD25 -cells, competition between the retrovirally introduced Foxp3 and naturally expressed AP-1 for NFAT binding could be an important event for lineage determination.…”
Section: Discussionsupporting
confidence: 86%
“…Basically, this finding implicates that exon 2 (aa 71-105) does not contain important sites influencing the function of human Foxp3. In fact, not only the DNA-binding forkhead domain, but also the recently described NFAT binding sites of Foxp3, are not located at the N terminus [22]. Nevertheless, aa 27-132 of human Foxp3 were recently suggested to contain a transcriptional repressor domain [24].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these experiments strongly suggest that N-Ras and K-Ras signaling play an important role in the control of Foxp3 + Treg. Although post-transcriptional effector mechanisms of Foxp3 remain elusive, it was recently suggested that Foxp3-related antiinflammatory programs rely on the formation of complexes with NFAT, which imposes a repressive signal on the IL-2 promoter [7]. Accordingly, we chose to assay NFAT in most assays involving Ras inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…It belongs to the forkhead protein family and is principally viewed as a repressor of genes that promote inflammation [6]. Full-length Foxp3 is encoded by 11 exons and contains a forkhead DNA-binding domain at the C terminus that acts by forming a repressor complex with nuclear factor of activated T cells (NFAT) [7]. This complex can bind in turn to the IL-2 promoter and repress transcription of IL-2 mRNA.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it has been reported that NFAT1 interacts with the transcription factor Foxp3 in the epigenetic regulation of genes involved in T reg differentiation. Disrupting this NFAT1:Foxp3 complex prevents the immunosuppressive function of Foxp3 1 T reg cells [23]. Furthermore, CD4 1 T cells from NFAT1/NFAT4 double-deficient mice are resistant to T reg -mediated immunosuppression [24].…”
Section: Transcriptional Regulation Of E3 Ligases In T-cell Tolerancementioning
confidence: 99%